Phylogenetic assessment of Apophallines (Digenea: Opisthorchiidae) with revision of Apophallus donicus Skrjabin & Lindtrop, 1919 complex and some taxonomic propositions. Issue 1 (31st December 2023) - Sokolov, Sergey G.; Khrustalev, Alexander V.; Greenwood, Spencer J.; Gray, Caitlyn N.; Robbins, William T.; Jones, Megan E. B.; Voropaeva, Ekaterina L.; Kalmykov, Alexander P.; Dzhamirzoev, Gadzhibek S.; Atopkin, Dmitry M.
Abstract : According to the current taxonomic concept, the Аpophallinae Ciurea, 1924 is a monotypic subfamily of the Opisthorchiidae that comprises species with a median permanent ventrogenital sac containing a well-developed ventral sucker and two gonotyls. A recently formulated molecular hypothesis suggests polyphyly of this subfamily and the presence of two sibling species within one of the nominal species A. donicus Skrjabin & Lindrop, 1919 . In this paper, we redescribed A. donicus s. str . and renamed A. donicus auct. non Skrjabin & Lindrop, 1919 to A. lari (Leonov, 1957 ) based on morphological, biological and molecular (mitochondrial cox1 gene fragments) data. The main morphological differences between species are the length of the distance between the anterior end of the body and the anterior extremity of the vitellarium as a ratio to the forebody length, and the shape of the anterior vitelline follicles. We also aimed to test the monophyly of the Аpophallinae through nuclear-ribosomal molecular markers 18S + 28S rDNA. Tree topology showed Apophallus zalophi (Price, 1932 ) clustered closer to Liliatrema Gubanov, 1953 than to the other Apophallus spp. As a result, we resurrect the genus Pricetrema Ciurea, 1933 that earlier was proposed for A. zalophi and abolish the Liliatrematinae Gubanov, 1953 with removal of Liliatrema into the Apophallinae. Thus, according to the updated concept, the Apophallinae contains three genera, Apophallus Lühe, 1909, Liliatrema and Pricetrema, two of which ( Apophallus, Pricetrema ) have the ventrogenital sac with two gonotyls and one ( Liliatrema ) has a genital sac without gonotyls.